2020
DOI: 10.1002/adsc.201901142
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Decarboxylative Synthesis of 5H‐Benzo[4,5][1,3]oxazino[2,3‐a]isoindole‐5,11(6aH)‐Diones using 2‐Phenyl‐4H‐Benzo[d][1,3]oxazin‐4‐Ones and α‐Oxo Carboxylic Acids

Abstract: A Pd-catalyzed novel and efficient protocol has been developed for the direct functionalization of 2-phenyl-4H-benzo[d][1,3]oxazin-4-ones with α-oxo carboxylic acids resulting in 5H-benzo[4,5][1,3]oxazino [2,3-a]isoindole-5,11(6aH)-diones using (NH 4 ) 2 S 2 O 8 as effective oxidant and AgNO 3 as co-oxidant. All the explored substrates were found to be compatible for this transformation and delivered the corresponding desired products in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…To our knowledge, decarboxylative acylation of quinazolinone is not known till date. Very recently, Singh and co‐workers revealed that palladium catalyzed decarboxylative acylation of similar moiety, i. e. 2‐aryl‐4 H‐ benzo[ d ][1,3]oxazin‐4‐ones ( 2 ) produced 5 H ‐benzo[4,5][1,3]oxazino[2,3‐ a ]isoindole‐5,11(6a H )‐diones ( 3 ) instead of expected acylated product ( 4 ) (Scheme 1b) [15] . In this context and owing to the importance of synthetic modifications of medicinally interested quinazolinone structures, in this manuscript we disclose Pd‐catalyzed decarboxylative aroylation of 2‐aryl‐quinazolinone ( 5 ) which are endowed with inherent quinazolinone directing group using α‐oxocarboxylic acid (Scheme 1c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, decarboxylative acylation of quinazolinone is not known till date. Very recently, Singh and co‐workers revealed that palladium catalyzed decarboxylative acylation of similar moiety, i. e. 2‐aryl‐4 H‐ benzo[ d ][1,3]oxazin‐4‐ones ( 2 ) produced 5 H ‐benzo[4,5][1,3]oxazino[2,3‐ a ]isoindole‐5,11(6a H )‐diones ( 3 ) instead of expected acylated product ( 4 ) (Scheme 1b) [15] . In this context and owing to the importance of synthetic modifications of medicinally interested quinazolinone structures, in this manuscript we disclose Pd‐catalyzed decarboxylative aroylation of 2‐aryl‐quinazolinone ( 5 ) which are endowed with inherent quinazolinone directing group using α‐oxocarboxylic acid (Scheme 1c).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, motivating yield (48%) was observed after carrying the reaction in trifluorotoluene solvent (entry 12). Replacement of oxidant with Na 2 S 2 O 8 and (NH 4 ) 2 S 2 O 8 produced slightly lower yield (45 and 42%, entry [13][14] whereas use of O 2 , oxone and PhI(OAC) 2 failed to produce desired product (entry [15][16][17]. Gratifyingly, when trifluoroacetic acid (TFA) was used as additive (0.1 mL) the desired product 6 a was formed in 79% (entry 18).…”
mentioning
confidence: 99%
“…Singh and co-workers [97] reportedaPd-catalyzedd ecarboxylative free radicala pproach from various substituted 2-phenyl-4H-benzo[d][1,3]oxazin-4-ones and a-oxo carboxylic acids in the presence of (NH 4 )S 2 O 8 as the oxidanta nd AgNO 3 as co-oxidant (Scheme 43). As eries of controlled experimentsa scertained the formation of an acylatedi ntermediate, which is converted into the targeted product.T he reaction was also tested in the presenceo ft he free radicals cavenger (2,2,6,6-tetramethylpiperidin-1-yl)oxidanyl( TEMPO) suggestingt hat the first acylation step follows ar adicalpathway.…”
Section: Pd-catalyzed Olefination/alkylation/arylation-cyclizationmentioning
confidence: 99%
“…Singh and co‐workers [97] reported a Pd‐catalyzed decarboxylative free radical approach from various substituted 2‐phenyl‐4 H ‐benzo[ d ][1,3]oxazin‐4‐ones and α‐oxo carboxylic acids in the presence of (NH 4 )S 2 O 8 as the oxidant and AgNO 3 as co‐oxidant (Scheme 43). A series of controlled experiments ascertained the formation of an acylated intermediate, which is converted into the targeted product.…”
Section: Cross‐coupling: Annulation/cyclizationmentioning
confidence: 99%
“…In 2020, Singh et al. explored a palladium‐catalyzed C−N/C−C bond formation approach to isoindolinones from 2‐phenyl‐4 H ‐benzo[ d ][1,3]oxazin‐4‐one and α‐oxocarboxylic acids [56] . This transformation used (NH 4 ) 2 S 2 O 8 as effective oxidant and AgNO 3 as co‐oxidant.…”
Section: Pd(iii) Involved Reactionsmentioning
confidence: 99%